The influence of sharia compliance and company reputation on customer decisions in using the services of Indonesian Islamic banks in the city of Palembang with trust as an intervening variable - Sonia Ramadhan; Peny Cahaya Azwari; Rinol Sumantri (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the Islamic banking industry in Indonesia shows a positive trend, but customer decisions in using Islamic bank services are still influenced by various factors, including sharia compliance, company reputation, and trust. This study aims to analyze the influence of sharia compliance and company reputation on customer decisions in using the services of Bank Syariah Indonesia in Palembang City with trust as an intervening variable. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to 150 respondents of Bank Syariah Indonesia customers in Palembang City who were selected using purposive sampling techniques. Data analysis was carried out using the Structural Equation Modeling method based on Partial Least Square (SEM-PLS). The results of the study show that sharia compliance does not have a significant effect on customer decisions or trust, and is not able to be mediated by trust. On the other hand, company reputation has a positive and significant effect on customer decisions and trust, and trust has been proven to be able to mediate the influence of company reputation on customer decisions. In addition, trust also has a positive and significant effect on customer decisions. The conclusion of this study emphasizes that company reputation and trust are dominant factors in influencing customer decisions, while sharia compliance has not yet become the main consideration, so Islamic banking needs to strengthen its image and trust to increase customer interest